The Philippines America's forgotten friends - Bocca, Geoffrey (New York Parents' Magazine Press, 1974)
A history of the Philippines stressing its political development and its tragic struggle in World War II.
Bibliography: p. 175-176.
1
Keywords: Philippines -- History; Philippines -- Politics and government